2018
DOI: 10.1159/000495229
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lithium Sensitive Orai1/ STIM1 Expression and Store Operated Ca2+ Entry in Chorea-Acanthocytosis Neurons by NF-κB Inhibitor Wogonin

Abstract: Background/Aims: The neurodegenerative disease Chorea-Acanthocytosis (ChAc) is caused by loss-of-function-mutations of the chorein-encoding gene VPS13A. In ChAc neurons transcript levels and protein abundance of Ca2+ release activated channel moiety (CRAC) Orai1 as well as its regulator STIM1/2 are decreased, resulting in blunted store operated Ca2+-entry (SOCE) and enhanced suicidal cell death. SOCE is up-regulated and cell death decreased by lithium. The effects of lithium are parallele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…We showed that STIM2 is upregulated in HD76 neurons and the pre-incubation of HD76 neurons with EVP4593 resulted in lowering the STIM2 level (Figures 4A,B). This result correlates well with the published data, demonstrating the attenuation of both lithium-induced and normal STIM2 expression by application of another NF-κB antagonist wogonin (Sukkar et al, 2018). Then we hypothesized that STIM2 drives the high activity of SOC channels in HD.…”
Section: Discussionsupporting
confidence: 91%
“…We showed that STIM2 is upregulated in HD76 neurons and the pre-incubation of HD76 neurons with EVP4593 resulted in lowering the STIM2 level (Figures 4A,B). This result correlates well with the published data, demonstrating the attenuation of both lithium-induced and normal STIM2 expression by application of another NF-κB antagonist wogonin (Sukkar et al, 2018). Then we hypothesized that STIM2 drives the high activity of SOC channels in HD.…”
Section: Discussionsupporting
confidence: 91%
“…and FGF23 total RNA was extracted according to manufacturer's instructions with TriFast (Peqlab, Erlangen, Germany) [60][61][62][63][64] . DNAse digestion was performed to avoid DNA contamination and was followed by reverse transcription using random hexamers (Promega, Manheim, Germany) and GoScript ™ reverse transcription system (Promega, Manheim, Germany).…”
Section: Quantitative Pcr To Determine Transcript Levels Of Nfat5 Omentioning
confidence: 99%
“…Western blotting. Protein abundance of NFAT5, ORAI1, and GAPDH was determined by Western blotting [60][61][62][63][64] . After isolation of platelets from control donors and patients with impaired kidney function, platelets were centrifuged for 5 minutes at 600 g and 4 °C.…”
Section: Quantitative Pcr To Determine Transcript Levels Of Nfat5 Omentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is extremely important that EVP4593 reduces excessive STIM2 levels to control values since it has been reported that downregulation of STIM2 can be dangerous because STIM2-dependent stability of mushroom spines was shown to be a mechanism of hippocampal synaptic loss in a mice model of Alzheimer’s disease [ 46 ]. Curiously, despite the expression of the STIM2 encoding gene, it does not depend on NF-κB; another blocker of NF-κB signaling, wogonin, can also reduce STIM2 levels [ 47 ]. Wogonin also inhibits the mTOR pathway and can have a similar effect as rapamycin on the STIM protein level [ 48 ].…”
Section: The Molecular Mechanisms Of Evp4593 Activitymentioning
confidence: 99%